2016
DOI: 10.1002/jmri.25559
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of active and inactive sacroiliitis in patients with ankylosing spondylitis using quantitative dynamic contrast-enhanced MRI

Abstract: 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:71-78.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
4
25
0
1
Order By: Relevance
“…This was attributed to in ltration of the in ammatory cells and pannus formation in the synovial area with increased microcirculation and greater capillary permeability. This result was consistent with that of Zhang et al [3] who found that K trans , K ep and V e of AS patients in the active group were signi cantly higher than those of AS patients in the inactive group patients using quantitative DCE-MRI.These results revealed that quantitative DCE-MRI parameters could differentiate between active and inactive AS.Higher K trans and K ep values are associated with increased microcirculation and greater capillary permeability of in ammatory tissues in the active sacroiliitis.Another previous study [23] has shown DCE-MRI parameters of the K trans ,k ep , and V e could be used to detect synovial in ammation in patients with early arthritis and correlated with synovial expression of the endothelial cell (EC) marker von Willebrand factor (vWF) ,which could facilitate the evaluation of joints inaccessible to next proper clinical examination.Our result was similar to the above report that quantitative DCE-MRI can provide performance for detecting early in ammation micro-environment permeability in SIJ of AS. In addition, there was a statistically signi cant positive correlation between the K trans , K ep ,V e with increasing weeks and changes in the K trans occurred earlier than K ep and V e .Based on our results,the K trans was more sensitive than the other parameters and it may has a potentially e cacy to predict early in ammatory activity more timely.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This was attributed to in ltration of the in ammatory cells and pannus formation in the synovial area with increased microcirculation and greater capillary permeability. This result was consistent with that of Zhang et al [3] who found that K trans , K ep and V e of AS patients in the active group were signi cantly higher than those of AS patients in the inactive group patients using quantitative DCE-MRI.These results revealed that quantitative DCE-MRI parameters could differentiate between active and inactive AS.Higher K trans and K ep values are associated with increased microcirculation and greater capillary permeability of in ammatory tissues in the active sacroiliitis.Another previous study [23] has shown DCE-MRI parameters of the K trans ,k ep , and V e could be used to detect synovial in ammation in patients with early arthritis and correlated with synovial expression of the endothelial cell (EC) marker von Willebrand factor (vWF) ,which could facilitate the evaluation of joints inaccessible to next proper clinical examination.Our result was similar to the above report that quantitative DCE-MRI can provide performance for detecting early in ammation micro-environment permeability in SIJ of AS. In addition, there was a statistically signi cant positive correlation between the K trans , K ep ,V e with increasing weeks and changes in the K trans occurred earlier than K ep and V e .Based on our results,the K trans was more sensitive than the other parameters and it may has a potentially e cacy to predict early in ammatory activity more timely.…”
Section: Discussionsupporting
confidence: 94%
“…Diagnosis of AS often depends on the clinical symptoms and imaging abnormities. Sacroiliitis is the most important clinical manifestation of AS [3] .However,there is high variability in clinical diagnosis and scoring systems that are mostly subjective. Evaluating active progression of AS by magnetic resonance imaging (MRI) had been widely accepted,which is a sensitive, non-invasive method that can permit the visualization of active and structural lesions,even in the absence of radiographically evident disease [4][5][6][7][8][9] .However,the DCE-MRI performance in AS simply used signal intensity changes over time to assess in ammation changes in the SIJ still remained subjective,limited by the inability to provide objective quantitative parameters,which was suggested as an imaging biomarker that is sensitive to disease progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 For patients with AS, DCE-MRI was shown to be a robust method to evaluate active disease and treatment efficacy in bones and entheses. 6,67 Thus, according to the reported evidence, the contribution of this technique in the diagnostic and therapeutic management of various inflammatory rheumatic diseases, and especially of RA, is already well known. As noted by the OMERACT group, regarding this latter disease, DCE-MRI may even replace the semiquantitative Rheumatoid Arthritis Magnetic Resonance Imaging Score (RAMRIS score) in the future.…”
Section: Dynamic Contrast-enhanced Magnetic Resonance Imagingmentioning
confidence: 99%
“…Post contrast fat suppression T1-weighted images as well as DCE-MRI have demonstrated its usefulness for SI detection with higher accuracy of the latter for detection of active disease even in the earliest phases[ 49 ].…”
Section: Clinical Scenariosmentioning
confidence: 99%